The EndoC-βH1 cell line is a valid model of human beta cells and applicable for screenings to identify novel drug target candidates - Violeta Georgieva Tsonkova; Fredrik Wolfhagen Sand; Xenia Asbæk Wolf; Lars Groth Grunnet; Anna Kirstine Ringgaard; Camilla Ingvorsen; Louise Winkel; Mark Kalisz; Kevin Dalgaard; Christine Bruun; Johannes Josef Fels; Charlotte Helgstrand; et al. (Elsevier, 2018)
Objective: To characterize the EndoC-βH1 cell line as a model for human beta cells and evaluate its beta cell functionality, focusing on insulin secretion, proliferation, apoptosis and ER stress, with the objective to assess its potential as a screening platform for identification of novel anti-diabetic drug candidates. Methods: EndoC-βH1 was transplanted into mice for validation of in vivo functionality. Insulin secretion was evaluated in cells cultured as monolayer and as pseudoislets, as well as in diabetic mice. Cytokine induced apoptosis, glucolipotoxicity, and ER stress responses were assessed. Beta cell relevant mRNA and protein expression were investigated by qPCR and antibody staining. Hundreds of proteins or peptides were tested for their effect on insulin secretion and proliferation. Results: Transplantation of EndoC-βH1 cells restored normoglycemia in streptozotocin induced diabetic mice. Both in vitro and in vivo, we observed a clear insulin response to glucose, and, in vitro, we found a significant increase in insulin secretion from EndoC-βH1 pseudoislets compared to monolayer cultures for both glucose and incretins.Apoptosis and ER stress were inducible in the cells and caspase 3/7 activity was elevated in response to cytokines, but not affected by the saturated fatty acid palmitate.By screening of various proteins and peptides, we found Bombesin (BB) receptor agonists and Pituitary Adenylate Cyclase-Activating Polypeptides (PACAP) to significantly induce insulin secretion and the proteins SerpinA6, STC1, and APOH to significantly stimulate proliferation.ER stress was readily induced by Tunicamycin and resulted in a reduction of insulin mRNA. Somatostatin (SST) was found to be expressed by 1% of the cells and manipulation of the SST receptors was found to significantly affect insulin secretion. Conclusions: Overall, the EndoC-βH1 cells strongly resemble human islet beta cells in terms of glucose and incretin stimulated insulin secretion capabilities. The cell line has an active cytokine induced caspase 3/7 apoptotic pathway and is responsive to ER stress initiation factors. The cells' ability to proliferate can be further increased by already known compounds as well as by novel peptides and proteins. Based on its robust performance during the functionality assessment assays, the EndoC-βH1 cell line was successfully used as a screening platform for identification of novel anti-diabetic drug candidates. Keywords: EndoC-βH1, Pseudoislets, Glucose stimulated insulin secretion, Somatostatin signaling, Proliferation